2017
DOI: 10.1016/j.jcis.2017.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of water-in-water emulsions by montmorillonite platelets

Abstract: The formation of water-in-water emulsions from the aqueous two phase system containing polyethylene oxide and pullulan, stabilised by montmorillonite platelets, was investigated. A novel approach of preparing the emulsions at non-equilibrium polymer concentrations was successfully utilised to control viscosity during mixing and allow the use of low energy emulsification methods. Polyethylene oxide adsorbed to the platelets much more strongly than pullulan favouring the formation of pullulan-in-polyethylene oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“… 29 The larger platelets also provide a greater barrier toward rotation, thus providing a more stable emulsion. 19 Using a droplet relaxation method, 81 , 83 the emulsion using large platelets also showed a drop in interfacial tension in comparison to the small platelet emulsion, indicating that surface area, and not simply a 2D shape, plays a key role in determining interfacial properties ( Table S4, Figures S17 and S18 ). It should be noted that, previously, small Gibbsite (clay) platelets at similar loading levels were shown to produce more stable emulsions than larger platelets.…”
Section: Resultsmentioning
confidence: 99%
“… 29 The larger platelets also provide a greater barrier toward rotation, thus providing a more stable emulsion. 19 Using a droplet relaxation method, 81 , 83 the emulsion using large platelets also showed a drop in interfacial tension in comparison to the small platelet emulsion, indicating that surface area, and not simply a 2D shape, plays a key role in determining interfacial properties ( Table S4, Figures S17 and S18 ). It should be noted that, previously, small Gibbsite (clay) platelets at similar loading levels were shown to produce more stable emulsions than larger platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these methods are very limited by the amount of cell spheroids that can be produced. Nguyen et al [23] and Ganley et al [24] showed that water-in-water Pickering emulsions could be stabilized by solid particles. A more comprehensive review on stabilization of w/w Pickering emulsion with colloid particles was published by Dickinson [25].…”
Section: Introductionmentioning
confidence: 99%
“…1820 Several other examples of stabilization of water-in-water emulsions using various nanoparticles have also been reported. 2123 However, these methods have some limitations and cannot be specifically applied to form every stable arbitrary ATPS emulsion. An alternative surfactant-free route to stabilize emulsions has been recently demonstrated by the group of Ulijn, who have generated stable oil-in-water emulsions by creating an interfacial compartmentalized gel network around the dispersed droplets.…”
Section: Introductionmentioning
confidence: 99%